2003
DOI: 10.1007/s00421-002-0728-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of timing of pre-exercise ingestion of carbohydrate on subsequent metabolism and cycling performance

Abstract: The occurrence of rebound hypoglycaemia may depend on the timing of carbohydrate intake. The aim of the present study was to investigate the metabolic and performance responses to the ingestion of carbohydrate at differing times before exercise. Eight subjects [mean (SEM)] [28 (3) years, 74.5 (2.6) kg, maximal oxygen uptake 63.1 (3.1) ml.kg(-1).min(-1)] performed three experiments. They ingested 75 g glucose dissolved in 500 ml water, thereafter resting for either 15, 45 or 75 min (15-Pre, 45-Pre and 75-Pre) b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
67
2
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(77 citation statements)
references
References 35 publications
4
67
2
2
Order By: Relevance
“…It was reported that CHO solution (such as glucose and maltodextrin) feeding before exercise can improve exercise performance through enhanced endurance exercise capacity (2,4,5,10). Moreover, it was also reported that CHO mixed meal feeding before exercise can improve endurance exercise capacity (7,9,11).The intake of CHO elevates the secretion of insulin from the pancreas into the blood. Glucose and insulin in plasma reach a peak approximately 30 min after the ingestion of CHO and thereafter gradually decrease to the basal level.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…It was reported that CHO solution (such as glucose and maltodextrin) feeding before exercise can improve exercise performance through enhanced endurance exercise capacity (2,4,5,10). Moreover, it was also reported that CHO mixed meal feeding before exercise can improve endurance exercise capacity (7,9,11).The intake of CHO elevates the secretion of insulin from the pancreas into the blood. Glucose and insulin in plasma reach a peak approximately 30 min after the ingestion of CHO and thereafter gradually decrease to the basal level.…”
mentioning
confidence: 99%
“…Fats are supplied by meals, and also by adipose tissues, but CHO must be acquired from meals before exercise because little is stored as glycogen in the liver or muscle tissue. Previous studies have been conducted on the ergogenic effects of CHO feeding before exercise (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). It was reported that CHO solution (such as glucose and maltodextrin) feeding before exercise can improve exercise performance through enhanced endurance exercise capacity (2,4,5,10).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, researchers have begun manipulating the timing of pre-exercise nutrition to determine the effects on subsequent exercise performance. 19 The majority of pre-exercise nutritional studies have examined carbohydrate-only administration in liquid form, and its subsequent effect on steady-state endurance cycling performance. 12,14 However, a liquid carbohydrate drink may not be representative of all pre-exercise nutritional practices, since many athletes may choose to consume a solid meal or energy bar and not necessarily a liquid carbohydrate drink.…”
Section: Introductionmentioning
confidence: 99%